1998
DOI: 10.1016/s0022-5223(98)70015-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates pyruvate dehydrogenase and protects human ventricular cardiomyocytes from simulated ischemia

Abstract: Insulin protected human ventricular cardiomyocytes from ischemia and reperfusion. This protection may be due to a stimulation of pyruvate dehydrogenase activity which resulted in improved aerobic metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 21 publications
2
38
0
3
Order By: Relevance
“…9 Insulin added to cardioplegic solutions in CABG patients enhances aerobic metabolism on reperfusion and improves left ventricular stroke work index. 17 Exogenous insulin also decreases oxidative stress and the inflammatory response. Low-dose infusions of insulin (2 IU/h) in obese patients significantly decreased levels of reactive oxygen species, adhesion molecules, and C-reactive protein within 2 hours.…”
Section: Discussionmentioning
confidence: 99%
“…9 Insulin added to cardioplegic solutions in CABG patients enhances aerobic metabolism on reperfusion and improves left ventricular stroke work index. 17 Exogenous insulin also decreases oxidative stress and the inflammatory response. Low-dose infusions of insulin (2 IU/h) in obese patients significantly decreased levels of reactive oxygen species, adhesion molecules, and C-reactive protein within 2 hours.…”
Section: Discussionmentioning
confidence: 99%
“…To verify anoxia, 2 ml of anoxic PBS was placed in a center dish within the sealed chamber and tested at the termination of each anoxic period to ensure a PO2 of 0 mmHg. Previous studies have demonstrated that this model of low-volume anoxia produced biochemical effects similar to the effects of clinical low-volume anoxia and reoxygenation (8,18,19,22,30,37,41). Heart cells reverted to anaerobic metabolism, producing lactic acidosis, a fall in ATP, and cell injury associated with the release of creatine kinase and troponin I.…”
Section: Experimental Model Of Low-volume Anoxia and Reoxygenationmentioning
confidence: 69%
“…These results suggest that cGMP-regulated K ATP channels are possibly important in L-arginine-mediated cardioprotection. Opening K ATP channels during reoxygenation after low-volume anoxia may facilitate the recovery of aerobic mitochondrial ATP production (8,18,30). Mitochondrial K ATP channel opening may improve electron transport (8).…”
Section: Effects Of L-arginine On Cellular Injury and No Production Amentioning
confidence: 99%
See 1 more Smart Citation
“…40 Hyperglycemia associated with insulin resistance has also been demonstrated in critically ill patients with no history of diabetes. 41 …”
Section: Pathophysiology Of Hyperglycemia In Critical Illnessmentioning
confidence: 99%